The Dystopian Past and the Disappointment with the 1990s in Ur varselklotet by Simon Stålenhag - Iuliano, Angela (Folia Scandinavica Posnaniensia, 2025)
Simon Stålenhag’s popularity has grown in recent years. Situated between picture books and anecdotal narration, his works have circulated widely and even inspired an American TV series. This paper focuses on Ur varselklotet (2014), a science fiction graphic book combining evocative images with short prose passages that both narrate personal anecdotes and serve as captions. The story recounts events from the narrator’s childhood and adolescence in the 1980s and 1990s, set against the backdrop of the Stockholm region. In a snowy landscape, the ruins of a fictional, now-abandoned particle accelerator, the world’s largest, loom: arch towers, metal spheres, and robotic machines blend seamlessly into the scenery. This analysis aims to explore how Stålenhag’s imagined architectures enable a rereading of Sweden’s political and economic history through a dystopian lens. Through visual and narrative elements, the author critiques Sweden’s transformation from a perceived “happy island” in Europe to a vulnerable state exposed to the consequences of 1990s neoliberal economic reforms. The dystopian imagery reflects disillusionment with a declining welfare system and the erosion of collective structures due to privatisation. Stålenhag thus uses retro-futurist aesthetics to comment on national identity, memory, and the socio-economic shifts of recent decades.